Adaptive Stakeholder Management in Social Startups: Enhancing Social Impact and Economic Sustainability - Aileen Mayda Dwina; Syahirul Alim (Pustaka Peradaban, 2024)
This research examines the implementation and outcomes of stakeholder relationship management (SRM) strategies in social startups, focusing on Indonesia's Social Organization Matchmaking program. Conducting by a qualitative approach, this study explores how the Outreach Campaign team designed and implemented SRM strategies to engage diverse Organizations within a resource-constrained, emerging market context. The findings highlight a multifaceted SRM approach encompassing strategic communication, personalized engagement, value co-creation, and digital interaction. This adaptive strategy significantly enhanced program outcomes, including a higher success rate in matching Organizations with sponsors, increased retention, and overall satisfaction. Key factors contributing to effective SRM were identified, such as fostering trust through transparent communication, cultivating commitment through shared value creation, and balancing digital and traditional engagement methods. Contextual factors, including cultural norms, economic realities, technological infrastructure, and regulatory environment, shaped SRM strategies.